SAT0287 Long-Term Safety Of Ustekinumab: 5 Years of Follow-Up from the Psoriasis Clinical Development Program Including Patients with Psoriatic Arthritis. (23rd January 2014) - Papp, K.; Griffiths, C.; Gordon, K.; Lebwohl, M.; Szapary, P. O.; Wasfi, Y.; Chan, D.; Shen, Y. K.; Ho, V.; Ghislain, P. D.; Strober, B.; Reich, K.
Abstract : Background: Ustekinumab(UST) is approved for moderate-to-severe psoriasis(PsO), and is currently in Phase 3 development for psoriatic arthritis(PsA). Objectives: We report the long-term safety experience of UST in the sub-group of PsO pts with a medical history of PsA(PsA Sub-group) compared with the overall PsO population (Overall Population) from the PsO development program with up to 5yrs of treatment and follow-up. Methods: Pooled safety data across one Phase 2 and three Phase 3[PHOENIX 1, PHOENIX 2, ACCEPT] clinical trials in pts with moderate-to-severe PsO were analyzed. Pts received UST45mg or 90mg SC 12wkly through up to 5yrs. The presence or absence of PsA (history of or current) at baseline was reported. No concurrent treatment for PsO or PsA was permitted throughout the studies, except for low potency topical steroids for PsO during the open-label long-term extensions of PHOENIX 1 and 2. Event rates for overall safety endpoints (adverse events [AEs], infections, AEs leading to discontinuation, serious AEs [SAEs]) and AEs of interest (serious infections, nonmelanoma skin cancers [NMSC], other malignancies, major adverse CV events [MACE]) were analyzed. All pts who received ≥1 dose of UST were included in the analyses. Data from the two UST dose groups were analyzed as a combined group. Results are expressed in events per 100 pt-years of follow-up (PY) and compared between the PsA Sub-group and Overall Population. Results: The Overall Population included 3117pts (8998 PY) who received ≥1dose of UST;with 1482 (47.5%) pts treated for ≥4yrs or more (including 838 [26.9%] for ≥5yrs). At baseline, the majority of pts were white (92.2%), male (68.5%), median age of 46yrs. Mean BSA involvement was 26.2%±16.7 and mean PASI score was 19.7±7.7; 27.5% of pts had concomitant PsA. Safety results for the PsA Sub-group and Overall Population are detailed in Table 1 . Through Yr5, event rates for overall safety endpoints and AEs of interest were generally comparable between the groups. Conclusions: With continuous UST exposure for up to 5yrs and approximately 9000 pt-years of follow-up in the PsO development program, long-term safety in the Overall Population were consistent with previous reports at earlier follow-up and event rates were generally comparable to other currently approved biologic agents. Long-term safety in the sub-group of PsO patients with a history of PsA at baseline were generally comparable to those in the overall study population. Disclosure of Interest: K. Papp Grant/research support from: Janssen Research & Development, LLC, C. Griffiths Grant/research support from: Janssen Research & Development, LLC, K. Gordon Grant/research support from: Janssen Research & Development, LLC, M. Lebwohl Grant/research support from: Janssen Research & Development, LLC, P. Szapary Employee of: Janssen Research & Development, LLC, Y. Wasfi Employee of: Janssen Research & Development, LLC, D. Chan Employee of: Janssen Research & Development, LLC, Y. Shen Employee of: Janssen Research & Development, LLC, V. Ho Grant/research support from: Janssen Research & Development, LLC, P. Ghislain Grant/research support from: Janssen Research & Development, LLC, B. Strober Grant/research support from: Janssen Research & Development, LLC, K. Reich Grant/research support from: Janssen Research & Development, LLC